A review on critical aspects of thermal shocks and thermal cycles in fiber reinforced polymer composites. (July 2023) - Jamshidi, Zahra; Hejazi, Sayyed Mahdi; Sheikhzadeh, Mohammad; Alirezazadeh, Azam
Fiber reinforced polymer composites (FRPCs) have gained great progress in a wide range of applications from construction and building structures to automobile and vehicle systems. During the operational lifetime, some FRPCs are exposed to various environmental conditions such as thermal cycles and thermal shocks. Fluctuation of the ambient temperature in the forms of thermal shocks or thermal cycles is one of the most important factors that deteriorate the durability and performance of the FRPCs. Compared to ceramic composites, less attention has been paid to the effects of thermal shocks and thermal cycles on the physical/mechanical properties of FRPCs. A comprehensive insight for the future advancements in this field is essential to possibly reduce the failure risks of FRPCs under thermal shocks and thermal cycles. The present work provides a comprehensive review on the physical/mechanical behavior of FRPCs under thermal cycles and thermal shocks. This work also provides a broad review on several factors that determines mechanical behavior of FRPCs, such as polymeric matrix, fiber type, incorporated nanofillers and fiber/polymer interface. Recent studies denoting important aspects and possible problems in mechanical performance of FRPCs under thermal shocks are also summarized.